MAKNA EKOKRITIK UNGKAPAN SUNGAI DALAM UJARAN SASTRA KALIMANTAN BARAT - Khairul Fuad (Handep: Jurnal Sejarah dan Budaya, 2021)
A river is an important part of the social and environmental management in West Kalimantan which becomes a marker of the community’s existence. Literature is the image of the management since it lives and develops according to its surrounding. The relationship between literature and rivers can be seen in the literary expressions The image of the river in literature changes over time which is seen in different expression of West Kalimantan’s poem. This paper used semiotic-dynamic as an analytical tool to find out the expressions of the river and its changes in literary expression. This analysis tool was used to obtain the dynamics of these literary expressions. In addition, an ecocritical method was also used to see the direction of river-related literary expression in West Kalimantan’s literature. The results show that the existence of rivers is an important pillar of people’s life in West Kalimantan as emphasized through literary works.